TileCode: Creation of Video Games on Gaming Handhelds - Ball, Thomas; Kao, Shannon; Knoll, Richard; Zuniga, Daryl (ACM Symposium on User Interface Software and Technology (UIST), 2020)
We present TileCode, a video game creation environment that runs on battery-powered microcontroller-based gaming handhelds. Our work is motivated by the popularity of retro video games, the availability of low-cost gaming handhelds loaded with many such games, and the concomitant lack of a means to create games on the same handhelds. With TileCode, we seek to close the gap between the consumers and creators of video games and to motivate more individuals to participate in the design and creation of their own games. The TileCode programming model is based on tile maps and provides a visual means for specifying the context around a sprite, how a sprite should move based on that context, and what should happen upon sprite collisions. We demonstrate that a variety of popular video games can be programmed with TileCode using 10-15 visual rules and compare/contrast with block-based versions of the same games implemented using MakeCode Arcade.